Development of a gamma irradiation loop to evaluate the performance of a EURO-GANEX process - I. Sánchez-García; H. Galán; A. Núñez; J.M. Perlado; J. Cobos (Nuclear Engineering and Technology, 2022)
A new irradiation loop design has been developed, which provides the ability to carry out radiolytic resistance studies of extraction systems simulating process relevant conditions in an easy and simple way. The step-by-step loop configuration permits an easy modification of settings and has a relative low volume requirement. This irradiation loop has been initially set up to test the main EURO-GANEX process steps: the lanthanide (Ln) and actinide (An) co-extraction followed by the transuranic (TRU) stripping. The performance and changes in the composition have been analyzed during the irradiation experiment by different techniques: gamma spectroscopy and ICP-MS for the extraction and corrosion behavior of the full system, and HPLC-MS and Raman spectroscopy to determine the degradation of the organic and aqueous solvents, respectively. The Ln and An co-extraction step and the corrosion that occurred during the first irradiation step revealed the favorable expected results according to literature. The effects of acidity changes occurred during the irradiation process, the presence of stainless corrosion products in solution as well as the new possible degradation compounds have been explored in the An stripping step. The results obtained demonstrate the importance of developing realistic irradiation experiments where different factors affecting the performance can be easily studied and isolated.